Study and Characterization of Nitration of Isovanillic Acid Derivatives using NMR and Mass Spectroscopy - Hermawati, Elvira; Sa'adah, Pipih Lutfi; Danova, Ade; Mujahidin, Didin; Musthapa, Iqbal (Departemen Kimia, 2025)
Isovanillic acid and its derivatives serve as precursors in the synthesis of EGFR tyrosine kinase inhibitors, which are used to treat cancer cell lines. A crucial step in this process is the nitration of isovanillic acid through nucleophilic aromatic substitution, resulting in 6-nitroisovanilic acid and its derivatives, which act as intermediates for forming a quinazolinone ring. However, this study revealed that direct nitration of isovanillic acid derivatives led to unexpected products, such as 3-hydroxy-4-methoxy-2,6-dinitrobenzoic acid (1) and 4-(3-(2-methoxy-4-nitrophenoxy)propyl)morpholine (4). Additionally, the optimal conditions for etherification of 2 with N-(3-chloropropyl)morpholine to produce 3 involved using Cs2CO3 in DMF and refluxing for 7 hours, achieving an 89% yield. All synthesized compounds were characterized using NMR spectroscopy, and mass spectrometry was employed for two compounds (3, 4). Compound 1 represents the first report of direct nitration of isovanillic acid. Compound 4 was synthesized for the first time from 3 through a one-pot process involving hydrolysis and decarboxylation, followed by nitration at carbon C-1 without metal catalysis, as confirmed by a NOESY 1D experiment. Moreover, the application of 4 could hold promise for future advancements in medicinal chemistry.